2008
DOI: 10.1128/jb.00130-08
|View full text |Cite
|
Sign up to set email alerts
|

RscS Functions Upstream of SypG To Control the syp Locus and Biofilm Formation in Vibrio fischeri

Abstract: Two-component signal transduction systems, composed of sensor kinase (SK) and response regulator (RR) proteins, allow bacterial cells to adapt to changes such as environmental flux or the presence of a host. RscS is an SK required for Vibrio fischeri to initiate a symbiotic partnership with the Hawaiian squid Euprymna scolopes, likely due to its role in controlling the symbiosis polysaccharide (syp) genes and thus biofilm formation. To determine which RR(s) functions downstream of RscS, we performed epistasis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
111
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(115 citation statements)
references
References 46 publications
4
111
0
Order By: Relevance
“…(i) SypG is a response regulator that is required for phenotypes induced by pRscS ϩ , including syp transcription and biofilm formation; it is predicted to be the direct transcriptional activator of the syp locus (16, 50). (ii) SypE is a second response regulator, which appears to play both positive and negative roles in biofilm formation (16,27). (iii) SypF, a predicted sensor kinase, also influences biofilm formation (5).…”
mentioning
confidence: 99%
“…(i) SypG is a response regulator that is required for phenotypes induced by pRscS ϩ , including syp transcription and biofilm formation; it is predicted to be the direct transcriptional activator of the syp locus (16, 50). (ii) SypE is a second response regulator, which appears to play both positive and negative roles in biofilm formation (16,27). (iii) SypF, a predicted sensor kinase, also influences biofilm formation (5).…”
mentioning
confidence: 99%
“…This phenotype, like wrinkled colonies, is induced by rscS overexpression and depends upon the syp locus (17,23). Although we previously observed a strong correlation between the formation of wrinkled colonies and the formation of pellicles (17,20,23,25,26), this was not the case for the bmp mutant: despite being unable to form a wrinkled colony, the bmp mutant was competent to form a pellicle (Fig. 4).…”
Section: Figmentioning
confidence: 59%
“…These data suggested that while the bmp genes are not required for pellicle formation per se, they may be involved in the maturation of the V. fischeri biofilm by building and/or maintaining the three-dimensional (3D) architecture of the biofilm. Additionally, because the syp locus is necessary for pellicle formation (20,23,25), these data suggested that the bmp mutant may still produce the Syp polysaccharide, a possibility that we address below.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations